Body image dissatisfaction among rural population: a systematic review - García Mendoza, Francelia (Mexican Journal of Medical Research ICSA, 2021)
Body image dissatisfaction, a risk factor for eating disorders, is no longer a phenomenon exclusive to developed countries or urbanized areas: the trend shows its expansion to other social sectors. The aim was to review the researches that have studied the presence of body image dissatisfaction in population from rural areas, describing both their methodology and the results obtained. A systematic review was carried out in PubMed, Google Scholar and Scopus, using key words such as: "body dissatisfaction", "body image", "eating disorders", "rural area/population". 27 papers that complied with the inclusion criteria were reviewed. All reported body image dissatisfaction, mainly tending to thinness. It is important to consider the contributions of the works presented here, pointing out the need to implement intervention strategies aimed equally at rural populations.